Significant Effect of the Central Bank Digital Currency on the Design of Monetary Policy - Muhammad Edhie Purnawan; Retno Riyanti (Jurnal Ekonomi Indonesia, 2019)
Entering the millennial era, technology has taken a big role in most sectors of life, including the currency as a product that can only be issued by the central bank. This paper examines the significant effect of central bank digital currency (CBDC) on the design of central bank monetary policy. The paper then sets out some benchmark central bank digital currency (CBDC) in several countries. Many central banks are actively exploring the initiation of sovereign digital currencies. Primary results this study is CBDC providing new monetary instruments, CBDC can improve financial inclusion, and CBDC is potential improvements in monetary policy transmission.